1999
DOI: 10.1001/archneur.56.7.809
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Subcortical Cerebral Infarction on Cortical Glucose Metabolism and Cognitive Function

Abstract: These results demonstrate that subcortical infarction produces global cerebral hypometabolism, which is related to the clinical status of the patients. In addition, specific frontal lobe hypometabolism also appears to be a feature of subcortical infarction. Taken together, both global and regional effects on cortical function mediate the production of clinical symptoms in patients with subcortical strokes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0
2

Year Published

1999
1999
2014
2014

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 89 publications
(47 citation statements)
references
References 57 publications
2
43
0
2
Order By: Relevance
“…This contradiction of GABA-A receptor expression in early and adult brain damage is not surprising since the motor cortex of congenital hemiplegia patients has shown increased metabolism (28) whereas decreased glucose metabolism has been shown in adults damaged by stroke (29). It is well known that cortical disinhibition promotes neural plasticity, especially practice-dependent plasticity (30).…”
Section: Discussionmentioning
confidence: 99%
“…This contradiction of GABA-A receptor expression in early and adult brain damage is not surprising since the motor cortex of congenital hemiplegia patients has shown increased metabolism (28) whereas decreased glucose metabolism has been shown in adults damaged by stroke (29). It is well known that cortical disinhibition promotes neural plasticity, especially practice-dependent plasticity (30).…”
Section: Discussionmentioning
confidence: 99%
“…In brief, fractal dimension within the CNS increases with childhood and adolescence, and then decreases in association with age, [44] which parallels the rise and fall in entropy production over the same time frames [77] as well as the decrease in glucose metabolism with age [72,81,82]. Moreover, fractal studies have demonstrated a decrease in fractal dimension of the CNS with illness (i.e., Alzheimer's [42], epilepsy [23,24], MS [45], stroke [49]) which correlates with metabolic studies demonstrating a decline in glucose metabolism with illness [83,85,88,[90][91][92][93][94][95][96][97][101][102][103]. Conversely, there are diseases which demonstrate an increase in fractal dimension including cancer [50][51][52][53][54][55] and grey matter structural changes in MS [46].…”
Section: Discussionmentioning
confidence: 67%
“…Early studies demonstrated a significant association between reduced ipsilateral cortical metabolism and the occurrence of aphasia or neglect following subcortical stroke [101,102]. Furthermore, studies have demonstrated that subcortical stroke produces global cerebral hypometabolism which has a negative correlation with cognitive function and clinical status of the patient [103]. Overall the loss of complexity and fractal dimension in the brain following stroke correlates with these metabolic studies, demonstrating a concomitant reduction in fractal dimension and cerebral metabolism as a consequence of stroke.…”
Section: Strokementioning
confidence: 97%
“…This is consistent with PET studies showing in SIVD hypometabolism and hypoperfusion in cortical regions, (6) especially in the frontal lobe. (7) In support of this view, MRS studies on animals have shown trans-synaptic decrease of NAA levels following acute deafferentation without neuronal loss. (8) It is therefore conceivable that the cortical [NAA] losses in SIVD could indicate deafferented neurons in a state of functional inactivity with a possibility for recovery rather than frank neuron loss.…”
Section: Subcortial Ischemic Vascular Dementiamentioning
confidence: 90%